Modulation of mitochondrial voltage dependent anion channel: studies on bilayer electrophysiology - Koren, Daniel Tuikhang; Malik, Chetan; Siddiqui, Shumaila Iqbal; Shrivastava, Rajan; Ghosh, Subhendu (Frontiers in Physiology, 2025)
The present paper is a review of the mitochondrial Voltage Dependent Anion Channel (VDAC), popularly known as mitochondrial porin, which is a protein that forms a passive diffusion ion channel across the outer membrane of the mitochondrion. VDAC essentially plays an important role in the transport of metabolites like ATP between the intermembrane space of the mitochondrion and the cytoplasm. However, under certain conditions, it can give rise to cellular dysfunction, e.g., apoptosis. Although VDAC is present in all eukaryotic cells, this review has focused mainly on the animal tissues. Interactions of VDAC with various enzymes, proteins, and small molecules or ligands have been reviewed with a perspective of bilayer electrophysiology. Importantly, the biochemical (post-translational) modifications of the channel protein, namely, phosphorylation (by a series of kinases), acetylation, ubiquitination, oxidative modifications (such as glutathionylation and nitrosylation), etc., and their impact on the electrophysiological properties have been discussed. Finally, the consequences of the above-mentioned experimental findings have been discussed with predictions and hypotheses relevant to living systems.